Hybrid APSOâSpiral Dynamic Algorithm - Hassan, S.M. (Springer, 2020)
The accelerated particle swarm optimisation (APSO) is an improved variant of the PSO algorithm that guarantees convergence through the use of only global best to update both velocity and position of particles. Â© 2020, Springer Nature Switzerland AG.